Correlation of Similarities and Differences in the Croatian and Serbian Languages - Bagdasarov, A. R.; Bychenko, A. A. (Вестник Кемеровского государственного университета, 2022)
The article introduces a comparative analysis of some interlingual variant formations in the linguistic structures of the Croatian and the Serbian literary languages. The general integration processes that occurred in the Slavic linguistic world in the XIX and the early second half of the XX centuries did not unite individual Slavic languages or their variants. By the end of the XX century, linguistic convergence was replaced by linguistic divergence. After the collapse of the Socialist Federal Republic of Yugoslavia, the new states that arose in the post-Yugoslavian space fixed the status of Croatian and Serbian as official languages. At present, Croatian and Serbian have their own codified norms; they develop and function autonomously and independently in different ethnic cultures and states. The widening gap between the post-Yugoslavian states of Serbia and Croatia contributed to the interlingual divergence between these languages. Their linguistic structure has multiple differences at phonetic, phonological, grammatical, lexical, syntactic, and stylistic levels. This research showed that the most prominent differences occur at the lexical level. As for linguistic standardization and codification, the Croatian language reveals a prescriptive-descriptive approach to language regulation, while Serbian is characterized by a descriptive-prescriptive approach. The authors illustrate this conclusion by various intervariant or equivalent language units from parallel reference books and online discourse.